2019
DOI: 10.1080/21691401.2019.1614595
|View full text |Cite|
|
Sign up to set email alerts
|

Angelica polysaccharide mitigates lipopolysaccharide-evoked inflammatory injury by regulating microRNA-10a in neuronal cell line HT22

Abstract: Background: Angelica polysaccharide (AP) is disengaged from the roots of Angelica sinensis. The extensive pathological activities of AP have been discovered in disparate diseases. Nevertheless, the impression of AP in epilepsy (EP) remains unaware. The research attempted to probe the impact of AP on lipopolysaccharide (LPS)-evoked inflammatory injury in HT22 cells. Methods: AP were exploited to stimulate HT22 cells, cell cytotoxicity was monitored by CCK-8 assay. LPS was utilized to administrate HT22 cells to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Accumulating evidences have con rmed the anti-in ammatory effect of AP. For example, AP mitigated the in ammatory injury induced by LPS in PC-12 cell line [17] and neuronal cell line HT22 [18]. Another study also proved that AP alleviated the LPS-induced in ammatory injury of human keratinocytes HaCaT cells [19].…”
Section: Introductionmentioning
confidence: 83%
“…Accumulating evidences have con rmed the anti-in ammatory effect of AP. For example, AP mitigated the in ammatory injury induced by LPS in PC-12 cell line [17] and neuronal cell line HT22 [18]. Another study also proved that AP alleviated the LPS-induced in ammatory injury of human keratinocytes HaCaT cells [19].…”
Section: Introductionmentioning
confidence: 83%
“…Besides antioxidation, it might inhibit the growth of KCs via enhancing activation of cleaved caspase-3 and PARP and improve depression via activating the ERK-CREB-BDNF signaling pathway (34)(35)(36). Angelica Sinensis polysaccharide could attenuate inflammation by repression of NF-jB and JAK2/STAT3 pathways (24,37). Astilbin was found to improve differentiation in HaCaT KCs with suppression of KRT5 and KRT14 and induction of KRT1 and KRT10 (25,26,38).…”
Section: Potential Pharmacological Mechanisms Of Action Of Tcm Ingredmentioning
confidence: 99%
“…A large number of clinical trials have confirmed that TCM can alleviate psoriatic symptoms (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Moreover, the applications of advanced analysis and detection technology reveal some of the therapeutic mechanisms behind TCM's potency such as anti-angiogenesis, inducing KCs apoptosis and anti-inflammation (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…It also could attenuate inflammatory injury through up-regulating sirtuin 1(SIRT1) expression and activating the nuclear factor-erythroid 2-related factor (NrF2)/ heme oxygenase-1 (HO-1) pathway in HACaT cells induced by LPS. 54,55 The mechanism of anti-inflammatory activity is shown in Figure 4 and relevant pathways are summarized in Table 3.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%